Effective Antimicrobial StewaRdship StrategIES (ARIES): Cluster Randomized Trial of Computerized Decision Support System and Prospective Review and Feedback. (29th June 2020) - Heng, Shi Thong; Wong, Joshua; Young, Barnaby; Tay, Hui Lin; Tan, Sock Hoon; Yap, Min Yi; Teng, Christine B; Ang, Brenda; Lee, Tau Hong; Tan, Hui Ling; Lew, Thomas W; Lye, David Chien; et al.
Abstract: Background: Prospective review and feedback (PRF) of antibiotic prescriptions and compulsory computerized decision support system (CDSS) are 2 strategies of antimicrobial stewardship. There are limited studies investigating their combined effects. We hypothesized that the use of on-demand (voluntary) CDSS would achieve similar patient outcomes compared with automatically triggered (compulsory) CDSS whenever broad-spectrum antibiotics are ordered. Methods: A parallel-group, 1:1 block cluster randomized crossover study was conducted in 32 medical and surgical wards from March to August 2017. CDSS use for piperacillin-tazobactam or carbapenem in the intervention clusters was at the demand of the doctor, while in the control clusters CDSS use was compulsory. PRF was continued for both arms. The primary outcome was 30-day mortality. Results: Six hundred forty-one and 616 patients were randomized to voluntary and compulsory CDSS, respectively. There were no differences in 30-day mortality (hazard ratio [HR], 0.87; 95% CI, 0.67–1.12), re-infection and re-admission rates, antibiotic duration, length of stay, or hospitalization cost. The proportion of patients receiving PRF recommendations was not significantly lower in the voluntary CDSS arm (62 [10%] vs 81 [13%]; P = .05). Appropriate indication of antibiotics was high in both arms (351/448 [78%] vs 330/433 [74%]; P = .18). However, in geriatric medicine patients where antibiotic appropriateness was <50%, prescription via compulsory CDSS resulted in a shorter length of stay and lower hospitalization cost. Conclusions: Voluntary broad-spectrum antibiotics with PRF via CDSS did not result in differing clinical outcomes, antibiotic duration, or length of stay. However, in the setting of low antibiotic appropriateness, compulsory CDSS may be beneficial.